2020
DOI: 10.3389/fgene.2020.544207
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal sdY Pseudogenes Explain Discordances Between Phenotypic Sex and DNA Marker for Sex Identification in Atlantic Salmon

Abstract: Despite the key role that sex-determination plays in evolutionary processes, it is still poorly understood in many species. In salmonids, which are among the best studied fishes, the master sex-determining gene sexually dimorphic on the Y-chromosome ( sdY ) has been identified. However, sdY displays unexplained discordance to the phenotypic sex, with a variable frequency of phenotypic females being reported as genetic males. Multiple sex determining loci in Atlanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 50 publications
5
21
0
Order By: Relevance
“…Similar to our findings, selffertilization of mature hermaphrodites has been recorded in estrogen treated rainbow trout, with 76.6% male offspring, suggesting viability of the YY genotype [24]. The YY genotype was confirmed among the offspring of the Golden Fish using a recently developed qPCR method [32], which confirmed 25% YY, 50% XY and 25% XX genotype distribution among the offspring from the selffertilization. Thus, the Golden Fish had a 1:1 ratio of X and Y eggs and sperm.…”
Section: Neo-female and Supermale Productionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our findings, selffertilization of mature hermaphrodites has been recorded in estrogen treated rainbow trout, with 76.6% male offspring, suggesting viability of the YY genotype [24]. The YY genotype was confirmed among the offspring of the Golden Fish using a recently developed qPCR method [32], which confirmed 25% YY, 50% XY and 25% XX genotype distribution among the offspring from the selffertilization. Thus, the Golden Fish had a 1:1 ratio of X and Y eggs and sperm.…”
Section: Neo-female and Supermale Productionsupporting
confidence: 90%
“…PCR products were visualized in 3% agarose gels. For distinguishing between XY and YY males we used the method recently described by [32].…”
Section: Genotypinggenetic Background/variation Sex and Vgll3mentioning
confidence: 99%
“…2012, 2013; Ayllon et al. 2020). Our results support this suggestion, as we found that the Rainbow Trout primer did not produce polymorphic bands in Brook Trout.…”
Section: Discussionmentioning
confidence: 99%
“…The third multiplex included the sex-specific markers, Exon 2 and Exon 4 [ 55 ] from the sdY sequence, a male-specific-Y-chromosome gene that is highly conserved in salmonids [ 56 ]. Although not always 100% accurate, due to the occasional occurrence of autosomal pseudocopies of sdY , at least in brown trout´s closest relative, Atlantic salmon [ 57 ], this provides more accurate sexing than phenotypic sex as morphological dimorphism can be difficult to ascertain in the field [ 58 ]. PCR was conducted using a Verity 96 well thermal cycler and GeneAmp PCR system 9700 (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%